Small RNA profiling reveals deregulated phosphatase and tensin homolog (PTEN)/phosphoinositide 3-kinase (PI3K)/Akt pathway in bronchial smooth muscle cells from asthmatic patients - Alexandrova, Elena; Miglino, Nicola; Hashim, Adnan; Nassa, Giovanni; Stellato, Claudia; Tamm, Michael; Baty, Florent; Brutsche, Martin; Weisz, Alessandro; Borger, Pieter (Journal of allergy and clinical immunology, 2016)
Aberrant expression of small noncoding RNAs (sncRNAs), microRNAs (miRNAs) and PIWI-interacting RNAs (piRNAs) in particular, define several pathologic processes. Asthma is characterized by airway hyperreactivity, chronic inflammation, and airway wall remodeling. Asthma-specific miRNA profiles were reported for bronchial epithelial cells, whereas sncRNA expression in asthmatic bronchial smooth muscle (BSM) cells is almost completely unexplored. We sought to determine whether the primary BSM sncRNA expression profile is altered in asthmatic patients and identify targets of differentially expressed sncRNAs. Small RNA sequencing was used for sncRNA profiling in BSM cells (from 8 asthmatic and 6 nonasthmatic subjects). sncRNA identification and differential expression analysis was performed with iMir software. Experimentally validated miRNA targets were identified by using Ingenuity Pathway Analysis, and putative piRNA targets were identified by using miRanda software. BSM cells from asthmatic patients showed abnormal expression of 32 sncRNAs (26 miRNAs, 5 piRNAs, and 1 small nucleolar RNA). Target prediction for deregulated miRNAs and piRNAs revealed experimentally validated and predicted mRNA targets expressed in the BSM cells. Thirty-eight of these mRNAs represent major targets for deregulated miRNAs and might play important roles in the pathophysiology of asthma. Interestingly, 6 of these mRNAs were previously associated with asthma, considered as novel therapeutic targets for treatment of this disease, or both. Signaling pathway analysis revealed involvement of 38 miRNA-targeted mRNAs in increased cell proliferation through phosphatase and tensin homolog and phosphoinositide 3-kinase/Akt signaling pathways. BSM cells of asthmatic patients are characterized by aberrant sncRNA expression that recapitulates multiple pathologic phenotypes of these cells.